Finite Element Study of MHD Impacts on the Rotating Flow of Casson Nanofluid with the Double Diffusion Cattaneo—Christov Heat Flux Model - Ali, Bagh; Naqvi, Rizwan Ali; Haider, Amir; Hussain, Dildar; Hussain, Sajjad (Mathematics (Basel), 2020)
A study for MHD (magnetohydrodynamic) impacts on the rotating flow of Casson nanofluids is considered. The concentration and temperature distributions are related along with the double diffusion Cattaneo–Christov model, thermophoresis, and Brownian motion. The governing equations in the 3D form are changed into dimensionless two-dimensional form with the implementation of suitable scaling transformations. The variational finite element procedure is harnessed and coded in Matlab script to obtain the numerical solution of the coupled nonlinear partial differential problem. The variation patterns of Sherwood number, Nusselt number, skin friction coefficients, velocities, concentration, and temperature functions are computed to reveal the physical nature of this examination. It is seen that higher contributions of the magnetic force, Casson fluid, and rotational fluid parameters cause to raise the temperature like thermophoresis and Brownian motion does but causes slowing the primary as well as secondary velocities. The FEM solutions showing an excellent correlation with published results. The current study has significant applications in the biomedical, modern technologies of aerospace systems, and relevance to energy systems.